Lack of prognostic significance of adiponectin immunohistochemical expression in patients with triple-negative breast cancer - Cubukcu, Erdem; Olmez, Omer Fatih; Kanat, Ozkan; Kabul, Selva; Canhoroz, Mustafa; Avci, Nilufer; Hartavi, Mustafa; Deligonul, Adem; Çubukçu, Sinem; Manavoglu, Osman (Contemporary Oncology/Współczesna Onkologia, 2014)
Introduction: Triple-negative breast cancers (TNBCs) – which lack the expression of estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER-2) – have no established markers that can be used for prognostic stratification. As adiponectin has been previously implicated in a more aggressive phenotype of primary bre-ast cancer, we explored the relation between adiponectin immunohistochemical expression and prognosis in TNBCs. Material and methods: Immunohistochemical staining for adiponectin was performed in 38 TNBC patients. Disease-free survival (DFS) and overall survival (OS) served as the main outcome measures. Results : Of the 38 TNBC patients, 18 (47%) had negative and 20 (53%) positive adiponectin immunohistochemical expression. We did not find any significant association between adiponectin immunohistochemical expression and the baseline characteristics. In addition, there were no associations between adiponectin immunohistochemical expression and prognosis. Conclusions : Although our results suggest that adiponectin immunohistochemical expression is not of prognostic significance in TNBCs, further studies are warranted to determine the role of this adipokine in breast cancer biology.